Exploring Capacity and Professional Development Needs of Teachers: Moving Toward Inclusive and Engaging Physical Education for Girls - Danielle Bianca Bates; Serene Kerpan (Education Sciences)
The purpose of this study was to understand teachers’ knowledge, perspectives, and experiences on inclusive and engaging physical education (PE) for girls, for the development of teacher professional development (PD). Through grounded theory qualitative research, this study explored teachers’ capacity and PD needs for including and engaging girls in PE. Data were collected from 10 Ontario teachers (N = 10) through two semi-structured focus groups and five semi-structured individual interviews. Themes were generated from the data indicating that teachers’ capacity to engage and include girls in PE is multifaceted and is influenced by numerous intrapersonal and institutional factors. While teacher participants employed a variety of evidence-based practices, notable gaps remained—particularly in their PE knowledge, inclusive pedagogical approaches, and confidence in their teaching abilities in a PE environment. This research provides insight for future PD to support teachers in engaging girls in PE.